PENGEMBANGAN PEMBELAJARAN PANTUN BERKAIT DENGAN MODEL PROJECT BASE LEARNING (PjBL) - salamah, umi; Rokhyanto, Rokhyanto; Muliyono, Nurwakhid (Jurnal Pembelajaran Sastra, 2023)
Pantun (rhymes) is an ancient poetry of Indonesia's intangible cultural heritage. This research aims to develop learning innovations related rhymes by PjBL model with a contextual approach and sociodrama methods. This research uses a qualitative approach and the Borg & Gall development method. Data collection techniques use diagnostic tests, observations and projects, while data analysis techniques use a flowing analysis model. Data verification was used using triangulation techniques. The research data source is junior high school students. Research Location in Malang. The results of data analysis show (1) the implementation of the PjBL learning model with a contextual approach, 98% of learners can make the cover and content of vocabulary used in daily conversations; (2) implementation of the PjBL learning model with a contextual approach and sociodrama method for learning related rhymes 100% complete. Students can change dialogue into related rhymes for role playing. The learning atmosphere is conducived and full of joy. Thus, it is concluded that the implementation of the development of the PjBL learning model with a contextual approach and sociodrama method creates an active, dynamic, fun and meaningful learning atmosphere. With these findings, it is recommended that secondary school teachers can use these findings for learning rhymes so that they are fun and meaningful for students, so that the nation's cultural heritage can be preserved and students' communication becomes more characterful and polite.